1995
DOI: 10.1287/isre.6.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Information Technology Usage: A Test of Competing Models

Abstract: The Technology Acceptance Model and two variations of the Theory of Planned Behavior were compared to assess which model best helps to understand usage of information technology. The models were compared using student data collected from 786 potential users of a computer resource center. Behavior data was based on monitoring 3,780 visits to the resource center over a 12-week period. Weighted least squares estimation revealed that all three models performed well in terms of fit and were roughly equivalent in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

287
4,956
41
244

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 6,282 publications
(5,528 citation statements)
references
References 44 publications
287
4,956
41
244
Order By: Relevance
“…The measure of behavioral control was almost identical to the measure applied by Battacherjee (2000) and Taylor and Todd (1995) because two of their original items were used; "I feel free to use MMS as I like" and "Using MMS is entirely within my control".…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measure of behavioral control was almost identical to the measure applied by Battacherjee (2000) and Taylor and Todd (1995) because two of their original items were used; "I feel free to use MMS as I like" and "Using MMS is entirely within my control".…”
Section: Methodsmentioning
confidence: 99%
“…The items were similar to those used by, e.g. Taylor and Todd (1995) and included the bipolar adjectives "bad/good", "foolish/wise", "unfavorable/favorable", and "negative/positive". Finally, intention to use was measured by a two-item scale adapted from Battacherjee (2000) and Mathieson (1991).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(p.458) Furthennore, the direct contributions (effects) of subjective nonn and attitudes to explaining usage in our study (see Figure 2) and to intentions to use in the Hartwick and Barki (1994) study are along the same direction, with attitude having a stronger direct effect on behavior than subjective norm in both studies. Similarly, Taylor and Todd (1995) report that the factors affecting behavioral intent, in order of the strength of their influence, were attitude, perceived behavioral control, and subjective norm. Our study also found the same level of impact on behavior, from highest to lowest, for the direct effects of attitude, voluntariness (corresponding to perceived behavioral control), and subjective norm.…”
Section: Limitationsmentioning
confidence: 99%
“…Varyanslar arasındaki yaklaşık %3'lük değişim, çalışmaların farklı kültürlerde ve farklı özellikler gösteren örneklemlerle yapılmış olmasından kaynaklandığı düşünülmektedir. Bunun yanında, BT öğretmen adaylarının ÇSA'lar için belirttikleri bu görüşlerden yararlanılarak geliştirilen dört faktörlü bu ölçek yapısının alanyazındaki birçok farklı teknoloji kabul modeli çalışmaları ile de tutarlılık gösterdiği görülmektedir (Davis, 1985;Sert ve Koçak Usluel, 2009;Taylor & Todd, 1995;Venkatesh & Davis, 2000). Bu çalışmalarda, yapıların isimlendirilmesi ve önem sıralaması modelden modele değişmekle birlikte, yeni bir teknolojinin kullanıcılar tarafından kabulü ve benimsenmesinde sözü edilen bu ortak yapıların etkili olduğu öne sürülmüştür (Venkatesh ve ark., 2003).…”
Section: Tartışma Ve Sonuçunclassified